The Molecular Pathways of Pyroptosis in Atherosclerosis - Song, Dan; Li, Manman; Yu, Xue; Wang, Yuqin; Fan, Jiaying; Yang, Wei; Yang, Liming; Li, Hong (Frontiers in Cell and Developmental Biology, 2022)
Atherosclerosis (AS) is a chronic inflammatory disease seriously endangering human health, whose occurrence and development is related to many factors. Pyroptosis is a new type of programmed cell death discovered in recent years, which is associated with an inflammatory response to participate in the formation and progression of AS. An increasing amount of research shows that pyroptosis affects the occurrence and development of AS by activating different signaling pathways. Protein modifications involved in sirtuin family and microRNA (miRNA) can directly or indirectly affect pyroptotic death-related molecules. This article will systematically review the involvement of pyroptosis in the pathogenesis of AS, as well as the the role of molecular pathways of pyroptosis in AS, which can provide a new perspective for AS prevention and treatment.